2008
DOI: 10.3386/w13898
|View full text |Cite
|
Sign up to set email alerts
|

The Transition to Post-industrial BMI Values Among US Children

Abstract: Abstract:Background: The trend in the BMI values of US children has not been estimated very

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 23 publications
(33 reference statements)
2
29
0
2
Order By: Relevance
“…The difference between the two distributions in the 1930s and in (2009) suggest that this skewing phenomenon has been taking place from 1980 onward in the case of Switzerland. We were not able to test that point in time, but we confirm the general pattern that has been observed in other countries (Rasmussen et al, 1999;Felgal and Troiano, 2000;Katzmarzyk, 2002;Penman and Johnson, 2006;Komlos et al, 2009;Hiermeyer 2009). The BMI distribution in Switzerland has become increasingly skewed in the second half of the twentieth century by a distribution shift more to the upper end of the curve than to the lower end.…”
Section: Methodsmentioning
confidence: 50%
See 3 more Smart Citations
“…The difference between the two distributions in the 1930s and in (2009) suggest that this skewing phenomenon has been taking place from 1980 onward in the case of Switzerland. We were not able to test that point in time, but we confirm the general pattern that has been observed in other countries (Rasmussen et al, 1999;Felgal and Troiano, 2000;Katzmarzyk, 2002;Penman and Johnson, 2006;Komlos et al, 2009;Hiermeyer 2009). The BMI distribution in Switzerland has become increasingly skewed in the second half of the twentieth century by a distribution shift more to the upper end of the curve than to the lower end.…”
Section: Methodsmentioning
confidence: 50%
“…The reason for this modern obesity pandemic remains quite enigmatic. Komlos et al (2009) found that the raising obesity pandemic among US-born children and youth since the 1920s and especially between 1950 and . We suggest that a positive energy balance (decreased energy expenditure by low level of physical activity and/or increased dietary energy intake by relative cheapness of processed foods, large portion sizes, immediate availability of fast foods, high-fat or high-energy diet and so on) is also a major reason for the increased prevalence of overweight Swiss from the 1980s until today; however, the phenomenon has been delayed by at least 30 years compared with the United States (Groscurth et al, 2003;Komlos et al, 2009;Statistisches Amt Basel Stadt, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Recent evidence also indicates that cross-country differences are larger in the right tail of the BMI distribution (Ruhm, 2007;Komlos et al, 2009).…”
Section: Data and Preliminary Evidence On The Spain Vs Italy Cross-cmentioning
confidence: 99%